(Supplement 4) Selective feeding of dinoflagellate in the Microscopy experiment - Meunier, Cédric Léo; Hantzsche, Florian; Cunha-Dupont, Alessandra; Haafke, Julia; Oppermann, Bettina; Malzahn, Arne; Boersma, Maarten (PANGAEA, 2021)
This dataset comprises data from two experiments analysed with two different tools, a FlowCam and a microscope. The heterotrophic dinoflagellate Oxyrrhis marina was subjected to different feeding treatments (starved, or fed with either F/2 nutrient reach, nitrogen-limited, or phosphorus-limited phytoplankton of the species Rhodomonas salina). The carbon:nitrogen:phosphorus stoichiometry of the different phytoplankton and dinoflagellate cultures was measured. The nitrogen-limited and phosphorus-limited phytoplankton were mixed and the mixture was offered as food to the dinoflagellates previously fed on either nitrogen-limited, or phosphorus-limited phytoplankton. The selective feeding of the dinoflagellate on the two mixed algal qualities was measured.